Moxifloxacin resistance is prevalent among Bacteroides and Prevotella species in Greece. - Papaparaskevas, Joseph; Pantazatou, Angeliki; Katsandri, Anastasia; Houhoula, Dimitra P; Legakis, Nicholas J; Tsakris, Athanassios; Avlamis, Athina (J Antimicrob Chemother, 2008)
OBJECTIVES: Moxifloxacin is recommended in the empirical treatment of infections involving Gram-negative anaerobes. However, current European data regarding its activity against anaerobic pathogens are limited. In order to evaluate its potency, we comparatively studied the activity of moxifloxacin against recently isolated Gram-negative anaerobes. METHODS: Four hundred and ninety-five Gram-negative anaerobic clinical isolates (296 Bacteroides fragilis group, 58 non-fragilis Bacteroides spp. and 141 Prevotella spp.) were prospectively recovered in six Greek hospitals. Moxifloxacin MICs were determined in comparison with those of penicillin, piperacillin/tazobactam, cefoxitin, imipenem, metronidazole and clindamycin. RESULTS: Overall moxifloxacin MIC(50) and MIC(90) were 2 and 32 mg/L, respectively. Based on the current CLSI breakpoints (susceptible, < or =2 mg/L; resistant, > or =8 mg/L), almost half of the total isolates (49%) were non-susceptible to moxifloxacin (32% resistant; 17% intermediate). This was more evident among the non-fragilis Bacteroides species, where 47% of the isolates were resistant and 14% intermediate to moxifloxacin. Species variation was noticed, with the highest non-susceptible rates detected among Prevotella oralis (90%), Prevotella bivia (80%), Bacteroides thetaiotaomicron (75%), Bacteroides uniformis (70%) and Bacteroides capillosus (67%) species. Among the 19 (4%) isolates that were metronidazole non-susceptible (MIC > or = 16 mg/L), only 4 (21%) were additionally non-susceptible to moxifloxacin. CONCLUSIONS: High resistance rates to moxifloxacin among Bacteroides and Prevotella spp. were recorded, exceeding those previously reported in Europe and contraindicating its use as monotherapy for infections involving Gram-negative anaerobes without prior microbiological confirmation. For empirical usage, moxifloxacin should be combined with metronidazole in order to cover for these pathogens.
Keywords: Adult; Anti-Bacterial Agents; Aza Compounds; Bacteroidaceae Infections; Bacteroides; Bacteroides Infections; Drug Resistance, Bacterial; Fluoroquinolones; Greece; Humans; Microbial Sensitivity Tests; Prevotella; Quinolines